INVESTIGATING mecA GENE EXPRESSION AND ITS MOLECULAR IMPACT ON METHICILLIN RESISTANCE INSTAPHYLOCOCCUS AUREUS (Journal of Medical & Health Sciences Review, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is a globally significant pathogen responsible for a wide range of hospital- and community-acquired infections. Its resistance to β-lactam antibiotics is primarily mediated by the mecA gene, which encodes the altered penicillin-binding protein PBP2a. This study aimed to investigate mecA gene expression in clinical isolates of S. aureus and evaluate its molecular impact on methicillin resistance. A total of 15 clinical isolates were analyzed, including 10 MRSA and 5 MSSA strains. Antibiotic susceptibility was determined using the broth microdilution method, while mecA detection was performed by conventional PCR. Quantitative real-time PCR (qRT-PCR) was used to assess mecA expression before and after exposure to methicillin at 64 µg/mL. RNA quality and cDNA synthesis efficiency were evaluated to ensure the reliability of gene expression analysis. All MRSA isolates displayed elevated methicillin MICs ranging from 32 to 128 µg/mL, while MSSA isolates showed low MICs (0.5–2 µg/mL) and tested negative for mecA. PCR amplification yielded a ~533 bp product in all MRSA strains. Upon methicillin exposure, mecA expression in MRSA increased significantly, with a fold change ranging from 6.2 to 12.4 (mean: 8.9-fold). RNA purity (A260/280 ~2.0) and qRT-PCR efficiency (96–104%) confirmed the validity of the data. No expression was observed in MSSA strains. These results confirm the inducible nature of mecA and its direct association with phenotypic methicillin resistance. This study reinforces the value of integrating molecular diagnostics with traditional susceptibility testing for accurate MRSA detection and monitoring.